The effectiveness of red ginger compress to prevent breast engorgement, reduce breast pain and prostaglandin hormone levels in postpartum mothers - Sari, Tatsa Putri Kumala; Wijayanti, Krisdiana; Anwar, M. Choiroel (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2022)
Background: The active ingredients of ginger, such as gingerol, shogaol, zingerone, and paradol, are compounds that play a significant role in anti-inflammatory and analgesic properties. Previous studies that have been carried out using red ginger showed significant results on the severity of breast engorgement; however, these studies have not measured the decrease in levels of the hormone prostaglandin, which is an indicator of engorgement and pain. Previous studies have also shown the impracticality of the intervention. This study has made red ginger "param" (medicinal powder to rub on the body), but the param formulation needs to be tested. Purpose: Analyze the effectiveness of red ginger compress in preventing breast engorgement and reducing breast pain and prostaglandin hormone levels in postpartum mothers. Methods: This is experimental research with a post-test only with a control group design. Respondents in this study were postpartum mothers. Respondents were randomly allocated into two groups, control groups (n=15) and intervention groups (n=15). The intervention group receives red ginger compresses twice daily for five consecutive days. The variables observed were breast engorgement, breast tenderness, and levels of prostaglandins. Data were analyzed using the independent T-test and Mann-Whitney test. Results: There was an effect of a red ginger compress to prevent breast engorgement (p<0.05) and reduce breast pain (p <0.05); however that is not significant reduce prostaglandin hormone levels (p>0.05). Conclusions: Red ginger compress effectively prevents breast engorgement and reduces breast pain, but not significant in reducing prostaglandin hormone levels.